DIFFERENTIAL DIAGNOSIS OF NOCTURNAL EPILEPTIC AND NONEPILEPTIC PAROXYSMAL PHENOMENA OF SLEEP IN ADULTS - S. G. Khachatryan; Yu. S. Tunyan (Эпилепсия и пароксизмальные состояния, 2016)
Abstract: major issues of differentiating epileptic and non-epileptic paroxysmal phenomena of sleep are presented in this article. Quality differentiation is possible in case of good knowledge of semiology of sleep-related epileptic seizure types and epileptic syndromes. Difficulties in identification can lead to further diagnostic mistakes. Parasomnias are the most frequently encountered non-epileptic paroxysmal events in sleep, which are related to both non-rapid-eye movement (NREM) sleep and rapid-eye movement (REM) sleep. NREM-sleep parasomnias are otherwise referred to as arousal disorders. They could be mistaken for frontal lobe epilepsy seizures, which predominantly occur at night and are not readily accompanied by epileptiformabnormalities on EEG. Other sleep phenomena also should be considered in differentiating nocturnal epilepsies. Obstructive sleep apnea, periodic leg movements in sleep and some sleep episodes sometimes are expressed with a pattern hardly distinguishable from epileptic seizures. Complex approach and appropriate diagnostic algorithm would further help clinicians in this field to better assess any given situation.